Hero vis-à-vis Author - Rrahmani, Kujtim (Respectus Philologicus, 2021)
This article examines the complex relationship between the hero and the author. Through a reflexive phenomenological tone, it is argued that the hero depicts the emotional seed of the subject itself while the author is the beautiful mind that projects events and worlds by cultivating the intellectual seed. The call of adventure as a ringing bell for the hero and the author, the proclaimed Death of the Author, the almost confirmed Death of the Hero, and the horizon of the Teacher’s Death are discussed. In this setting, the fear from the authority of the hero and the author remains imminent. This article attempts to move beyond the horizon of death certificates in order to reach primary frequencies at the nexus between author and hero, derived from the very inner tones of the human psyche that come as a call to take us away to the beautiful world of Aha Erlebnis. The author and the hero – they do matter.